Equine hepacivirus persistent infection in a horse with chronic wasting. Issue 5 (14th July 2017) - Elia, G.; Lanave, G.; Lorusso, E.; Parisi, A.; Trotta, A.; Buono, R.; Martella, V.; Decaro, N.; Buonavoglia, C.
Summary: Equine hepacivirus is the closest homologue of hepatitis C virus. Limited data on the clinical features of this infection are available. We report the identification of a horse with high‐titre viremia by equine hepacivirus. Over a 15‐month follow‐up, the clinical signs and the viremic status persisted, suggesting a chronic evolution.